Analysis of antibiotics use in pediatric pneumonia patients aged 3 months - 5 years - Aryani, Dhita Evi; Hasmono, Didik; Zairina, Nun; Setiawan, Landia (Folia Medica Indonesiana, 2017)
Pneumonia is an infectious disease that causes acute inflammation of the lung parenchyma and compaction exudate in the lung tissue. In addition to causing significant morbidity and mortality, pneumonia is also difficult to diagnose, treatments are less precise and less taken seriously. Pneumonia caused the death of 14% of children under five in Indonesia, with a mortality rate of 83 children per day. The difficulty of diagnosis, the selection of a less appropriate antibiotics, side effects, differences in pharmacokinetics and pharmacodynamics of the drug in infants and antibiotics resistance is to be a problem in itself. Therefore it is necessary to study the analysis of the use of antibiotics in patients with pneumonia of children aged 3 months till 5 years. The aim of this research to analyze antibiotics therapy in patients with pneumonia of children aged 3 months till 5 years. Method: an observational cohort analysis was carried out in the Pediatrics Respirology Division Dr. Soetomo Hospital Surabaya. Data was collected from February to May 2014. Patients who met the inclusion criteria were observed prospectively and the quantity and quality of antibiotics usage assessed with Gyssens category. Result: from February to May 2014 period, prospectively, the antibiotics usage quantitative evaluation used DDD/patient days shows that ampicillin 34.39DDD/100 patient days. Qualitative evaluation using Gyssens category on 75 antibiotics therapy shows that 32% considered appropriate. So, this study showed that ampicillin is most widely and qualitative analysis, only 32% of rational use of antibiotics.